Neoconstitutionalism and law constitutionalization - Ospina-Rendón, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This report aims to make clarifications on the concepts of neoconstitutionalism and law constitutionalization, topics that are in vogue among the experts in this area and, above all, that are as significant for the theory of the law, for the importance of the Constitution in a democracy and especially by the search of consolidation of a constitutional State.